Teachers’ agency during the Covid-19 lockdown: A new materialist perspective - Heikkilä Mirva; Mankki Ville (Routledge, Taylor & Francis Group, 2022)
Teachers’ agency is an essential factor in understanding and developing pedagogics. The study adds to the previous research by employing a new materialist perspective, highlighting the notion that teachers’ agency is not merely a matter of humans, but results from assemblages of both human and nonhuman elements in teaching. The context of the study is the school lockdown period of the Covid-19 pandemic. Twenty Finnish primary teachers were interviewed to explore how teachers verbalised the rapid transition to a distance teaching environment and to discern what kind of agency that transition unfolds. The findings illustrate lost agency, but simultaneously, new forms of agency emerging from the entanglement of humans and materiality in the changed assemblages. This understanding helps to support both preservice and in-service teachers’ agency in ways that acknowledge the complexity of teacher learning beyond individualistic and controllable views in increasingly multifaceted teaching environments.